Propuesta de comunicación para el posicionamiento de la imagen corporativa para el almacén AV Zarcero - Arrieta-Pérez, Katia (Instituto Tecnológico de Costa Rica, 2015)
The present research shows a communication plan for positioning the corporate image of Almacen Agroveterinario Dos Pinos in Zarcero area. This proposal is divided into two sections: the internal improvement plan and media plan. The internal improvement plan sets a number of proposals, focusing on the areas of staff, products and cargo area; to improve customer satisfaction and their shopping experience. This plan was developed based on the studies conducted in which customers determined the most important areas for improvement within the store. Similarly, the media plan was developed from the analysis of the tastes and preferences of customers, which was used to establish the profile of consumers who represent the target market. From this plan, resources were developed to achieve the positioning of the store in the area.
Proyecto de Graduación (Bachillerato en Administración de Empresas) Instituto Tecnológico de Costa Rica. Escuela de Administración de Empresas, 2015.
Keywords: Imagen corporativa; Mercadeo; Estrategia